Interaksi Epistemologi Bayani, Burhani, dan Irfani dengan Pendidikan Agama Islam: Tawaran Interconnected Entities - Afwadzi, Benny (Ma'arif Journal of Education, Madrasah Innovation and Aswaja Studies, 2023)
Islamic Religious Education (PAI, Pendidikan Agama Islam) faces various problems due to the hegemony of the bayani epistemology and the inadequate accommodation of the burhani and irfani epistemologies. Some of the issues that plague PAI include neglecting the historical realities of humanity, the presence of truth claims, stagnation in thinking, and difficulty in contextualizing other religious texts. This article contributes to resolving some of these problems in PAI through the interconnected entities model of Islamic epistemology. Employing a qualitative approach with a literature review, the authors made several findings. Firstly, the bayani epistemology draws from religious texts (the Qur'an and hadiths); the burhani epistemology relies on reason based on the realities (waqi') of nature, society, humanities, and religion; and the irfani epistemology derives from intuition through direct spiritual experiences. Secondly, interconnected entities are established by recognizing that each epistemology has the weaknesses, leading to a willingness to engage in dialogue, collaborate, and utilize methods and approaches employed by other epistemologies to complement these weaknesses. In the context of PAI, interconnected entities are carried out by collaborating on Al-Qur'an hadith, thought (pikir), and remembrance (zikir) to gain knowledge. Thirdly, the application of interconnected entities in PAI yields comprehensive knowledge. This is evident in the knowledge gained about the stages of human creation, specifically the concept of 'alaqah, which is more accurately understood as a zygote that attaches and depends on the uterine wall, rather than a mere clot of blood.